The Effect of Interruptions on Rapport Orientation in Formal Meetings - Reski Reski; Muhammad Aswad (EDUVELOP, 2018)
This research aims to find out the effects of interruptions on rapport orientations. The data of the research were obtained from two meetings held in an educational institution in Makassar. The data were collected through a video recording of the meetings to identify the interruption use performed by the meeting participants and by giving the meeting participants the questionnaire containing questions concerning the use of the interruptions in the meetings. The data were then transcribed and extracted into several parts to be analysed. The data were also obtained by carrying out a participant observation by which the researcher obtained the meeting participants’ perceptions and their responses on the use of the interruptions during the meetings. This research indicates that the interruptions have a number of effects on the rapport orientations. There are two types of interruptions, i.e. competitive and cooperative interruptions. The interruption effects are primarily regarding to the enhancement and threats to the three interconnected rapport components which are: face, social rights and obligations, and interactional goals. The interruptions occurring also have several roles in the meetings which are closely related to the rapport management like clarifying and supporting main speakers’ points in the meetings, as the way to do relational work and back-channeling of the statement of the main speakers resulting in the type of rapport orientations applied by the meetings’ participants.